Correction: Graphene-catalyzed photoreduction of dye molecules revealed by graphene enhanced Raman spectroscopy. Issue 9 (15th February 2016) - Lee, Bora; Kang, Jin Hyoun; Jo, Insu; Shin, Dongha; Hong, Byung Hee
Abstract : Correction for 'Graphene-catalyzed photoreduction of dye molecules revealed by graphene enhanced Raman spectroscopy' by Bora Lee et al., Phys. Chem. Chem. Phys., 2016, 18, 3413–3415.